Crucial roles of GATA-2 and SP1 in adrenomedullin-affected expression of tissue factor pathway inhibitor in human umbilical vein endothelial cells exposed to lipopolysaccharide - Liu, Wei; Zhu, Zi-Qiang; Wang, Wen; Zu, Shu-Yu; Zhu, Guang-Jin (Thrombosis and Haemostasis, 2007)
Adrenomedullin (ADM) is a vasodilator peptide that has a variety of effects, including antithrombotic activities and resistant roles to lipopolysaccharide (LPS)-induced septic shock. During sepsis,LPS triggers the development of disseminated intravascular coagulation (DIC) via the tissue factor-dependent pathway of coagulation.It is unknown whether the antithrombotic activities of ADM contribute to its resistance to sepsis. In the present study, we investigated the effects of ADM on tissue factor pathway inhibitor (TFPI) (primary anticoagulant factor) expression in human umbilical vein endothelial cells (HUVECs) exposed to LPS,and the possible underlying mechanism for these effects.Exposure of HUVECs to LPS for 12 hours caused significant decrease of TFPI protein activities and mRNA expression.These effects were abolished by treatment withADM (10–10 to 10–6 M), cAMP analogue and calcium antagonist. Accordingly, cAMP antagonist inhibited the counteraction effect of ADM on LPS in TFPI expression. Electrophoresis mobility shift assay (EMSA) and Western blot analysis showed that the protein level of GATA-2 and SP1 transcriptional factors and their binding to the corresponding regulatory sequences decreased by LPS treatment. And these effects of LPS were antagonized by ADM. Promoter- reporter assays and mutational analysis also confirmed the roles of GATA-2 and SP1 motifs from –1247 to –381bp promoter sequence in TFPI inducible expression. Taken together, these results indicate that ADM antagonizes the effect of LPS on TFPI expression, which is mediated by affecting transcriptional factor GATA-2 and SP1 through cAMP and calcium signaling pathway.
Keywords: Adrenomedullin; human umbilical vein endothelial cells; tissue factor pathway inhibitor; transcriptional factor